PENILAIAN TINGKAT KESEHATAN BANK UMUM SYARIAH DEVISA MENGGUNAKAN METODE RISK BASED BANK RATING (RBBR) PERIODE 2014-2016 - Monique, Eska Prima; Prawitasari, Andriani (JURNAL EKOMBIS REVIEW, 2018)
Banks face problems in determining business strategy in managing their business. this business strategy will then be used as the foundation and framework to realize the work goals that have been determined by management. In the past ten years, sharia banking has grown rapidly, especially since the issuance of statute no. 10 of 1998. This research uses three risk assessment method (Risk Based Bank Rating), which are risk profile aspect (NPL, LDR), earning ratio (ROA, NIM), and capital adequacy (CAR). As for the aspects of good corporate governance (GCG), it is not used because it requires primary data concerning bank secrecy. The sample population in this study is sharia foreign exchange bank. while the sampling method used purposive sampling (i.e. taking samples with certain criteria). The population for foreign exchange banks is 35, but this study only uses 5 sharia banks (based on predetermined criteria). Based on the results of this study the entire sample of Sharia Banking Foreign Exchange shows the results of CAR performance with a very healthy predicate. Although in 2015 the performance of Non Performing Loan (NPL) had decreased, but in 2016 all Sharia Foreign Exchange Banks were able to improve NPL performance to below 5% (healthy performance predicate). In 2014-2016, there are 4 out of 5 Sharia Foreign Currency Bankers performing Loan To Deposit Ratio (LDR) with a fairly healthy predicate (LDR is between 85% and 100%). Net Interest Margin (NIM) performance of all samples of Foreign Exchange Sharia Banking in 2014-2016 tends to be very healthy (NIM> 3%). So it can be said that the company is able to profit from interest income. During 2014-2016 the Return on Asset (ROA) performance of the Sharia Banking Foreign Exchange (ROA) sample also tended to increase, if in the previous two years (2014 and 2015) only 2 out of 5 sample banks have ROA above 1.25% then in 2016 there 3 out of 5 sample banks are able to achieve ROA performance even above 1.5% (very healthy predicate)